Role of multilateral development organizations, public and private investments in aquaculture subsector in Kenya - Munguti, Jonathan M.; Obiero, Kevin O.; Iteba, Jacob O.; Kirimi, James G.; Kyule, Domitila N.; Orina, Paul S.; Githukia, Cecilia M.; Outa, Nicholas; Ogello, Erick O.; Mboya, Jimmy B.; Ouko, Kevin O.; Liti, David; et al. (Frontiers in Sustainable Food Systems, 2023)
Rapid population and economic growth, increased health benefits of aquatic food, and changes in lifestyles and preferences as a result of rapid urbanization and globalization are all contributing to the rapid growth of aquaculture production in Kenya. Despite significant investment efforts from the national and devolved governments as well as donors and international organizations, smallholder aquaculture production is yet to result in a significant increase in incomes and improved food and nutrition security. We conducted a scoping review to investigate the roles of multilateral development organizations, international financial institutions, and public and private investments in Kenya’s aquaculture subsector. We draw on lessons learned from previous projects implemented at the national, county, and farm levels to make recommendations for sustainable aquaculture intensification in Kenya. To unlock Kenya’s aquaculture potential and improve its food and nutrition status, deliberate efforts must be made to create a conducive environment for public and private investment in the industry. First, there is a need to coordinate and clearly articulate the roles and responsibilities among devolved and national governments, donors, and financial institutions through public-private partnerships to ensure optimal allocation of financial, human, and infrastructure resources. Second, more collaborative research should be devoted to the design and construction of climate smart culture systems, developing new species to guarantee supply of high-quality products; developing and scaling low-cost and highly nutritious fish feeds based on novel ingredients; and enhancing resilient livelihoods through innovative aquaculture practices and market linkages to create employment opportunities for youth and women. Finally, the national and devolved governments should create an enabling policy environment through tax incentives and regulatory reforms to combat climate change, protect nature and biodiversity, sustain livelihoods, and mainstream food and nutrition initiatives into the design and implementation of future aquaculture projects.